Development of Equity Crowdfunding Platform Since the Approval of POJK No.37/POJK.04/2018 in Assisting IKN Infrastructure Development - Kushi Alifia Pratiwi; Bayu Rama Laksono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates the impact of equity crowdfunding on significant infrastructure projects in Indonesia, with a focus on those that fall under the regulatory framework outlined in POJK No. 37/POJK.04/2018. It addresses the following research question: How does equity crowdfunding contribute to Indonesia's infrastructure financing? Its narrow focus on the use of crowdfunding for infrastructure fills a gap in the literature, which often lacks empirical research unique to Indonesia. Using a mixed-method approach that combines qualitative insights from stakeholder interviews with quantitative analysis of crowdfunding data, the study finds that although equity crowdfunding has the potential to mobilize capital for infrastructure, obstacles include investor protection, regulatory compliance, and project scalability. The study emphasizes the crucial role of regulatory frameworks and specially designed financial products in determining the outcomes of crowdfunding. In the end, the study recommends changing policy to create an atmosphere that is favorable to crowdfunding, improving financial, and aiding Indonesia's sustainable development goals.